The Impact of Translation on Reading Comprehension for EST Learners - A Case Study of Computer Science Students at Constantine 2 University - Draa, Amer (Journal of Human Sciences, 2019)
We study the impact of introducing EST concepts for computer science learners through the use of translation. We have opted for the use of an on-the-fly translation, in which the teacher uses translation just to explain ambiguous terms or ideas related to the presented material if needed. To check the effect of using translation on EST learners’ comprehension abilities, we devised a test-based experimental study. The test and experiment groups, have been taught EST for one semester with the use and exclusion of translation into French/Arabic, respectively. A pre-test and post-test have been conducted. Then, a statistical analysis has been carried out. The obtained results have shown that the use of translation from English into the mother tongue of the learners, or into any other language the learners know, has a positive impact on the overall comprehension of the material provided in the EST course.